Investigating the potential of combined growth factors delivery, from non-mulberry silk fibroin grafted poly(ɛ-caprolactone)/hydroxyapatite nanofibrous scaffold, in bone tissue engineering. (December 2016) - Bhattacharjee, Promita; Naskar, Deboki; Maiti, Tapas K.; Bhattacharya, Debasis; Kundu, Subhas C.
Graphical abstract: Highlights: Non-mulberry silk fibroin was grafted onto nanofibrous PCL matrices. HAp was inculcated in these matrices via alternative soaking. HAp inclusion improved strength and biocompatibility of matrices. Carbodiimide coupling was used to load the composite scaffolds with growth factors. Dual growth factor loaded scaffold gave best cell growth and differentiation result. Abstract: Mineralized scaffolds have the advantage of better mimicking the natural bone structure and thus show an improved potential for bone tissue engineering. This study uses cycles of alternative soaking to deposit hydroxyapatite (HAp) layers upon non-mulberry silk fibroin (from Antheraea mylitta ) grafted poly(ɛ-caprolactone) nanofibrous matrices. Alternate soaking, of one through three cycles, is used due to its simplicity and deposition efficiency. HAp deposition improved mechanical strength of the scaffolds up to two cycles of soaking (by nearly 75%). Analysis of mechanical properties, bioactivity and in vitro study results (with MG-63 cell line) showed scaffolds fabricated using two-cycle soaking to be the most suitable. These constructs were loaded with growth factors (transforming growth factor beta (TGF-β) 4 ng and bone morphogenic protein-2 (rhBMP-2) 100 ng) using carbodiimide-coupling reaction. The following three different combinations of growth factor loaded composites were analyzed: solely rhBMP-2, solely TGF-β and rhBMP-2-TGF-β combinations. Scaffolds with both growth factors supported cellular activity and proliferation better ( p < 0.01), generated greater calcium deposits ( p < 0.01), facilitated early cell differentiation and yielded significantly better expression of genes linked to bone growth ( p < 0.05). These dual growth factor loaded scaffolds are mechanically robust and enhance cell proliferation and early differentiation of osteoblast-like cells. They thus show potential of being further optimized for use in bone tissue engineering.